IN VITRO PROPAGATION OF COSTUS PICTUS (D.DON.) - SANJAY BIRADAR; NARAYAN PANDHURE; PALLAVI PRASAD (International Journal of Pharma and Bio Sciences, 2013)
Costus pictus a valuable medicinally important ‘insulin plant’ cultivated in garden as an ornamental belongs to the family Costaceae. During present investigation Micropropagation studies in Costus have been tried using different growth hormones viz. BAP, KIN, IBA, IAA, and NAA. Nodal part of stem was tried and proven suitable for Micropropagation as compare to rhizome, rhizomatic eye, and apical shoot. Suitable combinations of growth regulators recorded for Micropropagation were 2.7 mg/L BAP, 0.2 mg/L IAA from the nodal region. Hence present findings provide the standard in vitro protocol for Costus pictus.